Elastyczność i innowacyjność a zachowania strategiczne przedsiębiorstw - Ćwik, Krzysztof (The strategic behaviours of enterprises and their flexibility and innovation process, 2007)
The article consider the problem of strategic behaviours of enterprises on their flexibility and innovation process. The basic questions of flexibility and innovation were confronted with strategies typology of Miles and Snow.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 43-52